Interleukin-23 secretion by donor antigen-presenting cells is critical for organ-specific pathology in graft-versus-host disease - Das, Rupali (American Society of Hematology, 2009)
Damage to the gastrointestinal tract during graft-versus-host disease (GVHD) from the conditioning regimen in conjunction with alloreactive donor T cells plays a pivotal role in the pathogenesis of this disease. In this study, we have identified secretion of interleukin-23 (IL-23) by donor antigen-presenting cells (APCs) as a critical event in the induction of GVHD of the colon linking conditioning regimen-induced mucosal injury and lipopoly-saccharide (LPS) translocation to subsequent proinflammatory cytokine production and GVHD-associated pathologic damage. In the absence of donor APC-derived IL-23 secretion, there is a selective and profound reduction in pathologic damage as well as a marked reduction in LPS and proinflammatory cytokine production in the colon microenvironment. The downstream proinflammatory effects of IL-23 are dependent upon donor-derived secretion of interferon-γ (IFN-γ), but are independent of donor IL-17 production. These findings define a novel organ-specific role for IL-23 in the pathophysiology of GVHD and demonstrate that IL-23 can direct tissue-specific pathology within the context of a systemic inflammatory disorder. Furthermore, these studies also identify IL-23 as a potential therapeutic target for the prevention of this life-threatening disorder.